THU0330 PREVALENCE OF RAYNAUD'S PHENOMENONIN THE NORTHERN PARTS OF THE NETHERLANDS: AN EPIDEMIOLOGICAL STUDY OF THE LIFELINES COHORT. (June 2019) - Abdulle, Amaal Eman; Brouwer, Elisabeth; Goor, Harry van; Roon, Anniek van; Westra, Johanna; Leeuw, Karina de; Mulder, Douwe J
Abstract : Background: Although several previously conducted studies reported on the prevalence of Raynaud's phenomenon (RP) in different regions of the world, these studies often included a limited number of selected individuals. Moreover, no studies exist that have systematically assessed the relative contribution of known etiological factors of RP in the general population of the Netherlands. Objectives: To assess the prevalence of RP, and gender-specific etiological factors associated with RP in the Northern parts of the Netherlands. Methods: Data from the Lifelines cohort were analyzed, in which all participants completed the self-administered validated connective tissue disease questionnaire. Subjects who reported cold-sensitive fingers and bi- or triphasic colour changes in response to cold were considered to suffer from RP. Known etiological factors such as hormonal status, body mass index (BMI), smoking behaviour, and comorbidities were all assessed in a standardised way. Results: In total 93935 participants completed the questionnaire (mean age 45.6 ±12.9). The prevalence of RP was 4.2% [95% CI 4.1-4.4] which was approximately three-fold higher in females (5.7%, 95% CI [5.5-5.9]), as compared to males (2.1%, 95% CI [1.9-2.2], p-value <0.001, figure 1 ). Regarding gender-specific risk factors associated with RP, we observed that BMI <18.5 (OR 4.6 [2.4-8.7], p<0.001), cardiovascular disease (OR 1.53 [95% CI 1.31-1.78], p<0.001), history of cancer (OR 1.40 [1.00-1.95], p=0.049), use of beta-blockers (OR 1.39 [1.06-1.83], p=0.01), and smoking (OR 1.28 [1.09-1.51], p=0.003) were associated with an increased odds of RP in men. Conversely, alcohol consumption, diabetes and age were not associated with RP in men. In females, BMI<18.5 (OR 2.9 [2.27-3.64], p<0.001), cardiovascular disease (OR 1.42 [1.32-1.54], p<0.001), receiving hormonal contraception (OR 1.17 [1.08-1.26], p<0.001), and hormonal replacement therapy (OR 1.14 [1.04-1.25], p=0.007) were associated with increased odds of RP. Moreover, smoking behavior, use of beta-blockers, alcohol consumption, and diabetes were not associated with RP in women. A BMI>30 was associated with a strongly decreased odds of RP in both men (OR 0.22 [0.11-0.42], p<0.001) and women (OR 0.35 [0.28-0.44], p<0.001). Conclusion: This large cohort study found a prevalence of 4.2% of RP in the Northern part of the Netherlands, with an expected predominance in young female subjects. Moreover, the etiologic risk factors of RP are multifactorial and clearly gender-specific (e.g., hormonal status in women, smoking behavior and use of beta-blockers in men), with underweight strongly increasing and obesity strongly decreasing the likelihood of RP in both sexes. This might suggest that different mechanisms influence the expression of RP in men and women. Disclosure of Interests: Amaal Eman Abdulle : None declared, Elisabeth Brouwer Speakers bureau: Dr. Brouwer as an employee of the UMCG received speaker fees and consulting fees from Roche which were paid to the UMCG, Harry van Goor: None declared, Anniek van Roon: None declared, Johanna Westra: None declared, Karina de Leeuw: None declared, Douwe J Mulder Grant/research support from: My University has received research grants for my research from: Boehringer Ingelheim and Actelion, Speakers bureau: My University has received speakers fee from: Sanofi